Phylogenic Diversity and Taxonomic Problems of the Dictyosphaerium Morphotype within the Parachlorella Clade (Chlorellaceae, Trebouxiophyceae). (16th November 2017) - Song, Huiyin; Wang, Qinghua; Liu, Xudong; Hu, Yuxin; Long, Jijian; Liu, Guoxiang; Hu, Zhengyu
Abstract: The Parachlorella clade was put forward as a group within the family Chlorellaceae in 2004. Recent molecular analyses have revealed that Dictyosphaerium morphotype algae form several independent lineages within the Parachlorella clade, and new genera and species have been established. In this study, we focus on the diversity of Dictyosphaerium morphotype algae within the Parachlorella clade, based on 42 strains from China. We used combined analyses of morphology and molecular data based on SSU and internal transcribed spacer region (ITS) rDNA sequences to characterize these algae. In addition, the secondary structure of ITS2 was compared to delineate new lineages. Our results revealed high phylogenic diversity of Dictyosphaerium morphotype algae, and we describe five distinct lineages. We examined the morphological features of these five lineages, and morphological differences are difficult to find compared with other Dictyosphaerium morphotype algae. The five distinct lineages were not described as new genera currently. We lastly discuss the taxonomic problems regarding the Dictyosphaerium morphotype within the Parachlorella clade, and possible solutions are considered.